Priming of defence signalling in grapevine cells depends on actin filaments - Ruipu Wang; Pingyin Guan; Michael Riemann; Peter Nick (Protoplasma, 2026)
Defence priming has attracted significant attention as a potential sustainable strategy to enhance plant immunity. In this study, we show that pre-treatment with aluminium ions can amplify the response of transcripts for phytoalexin synthesis and their transcriptional regulators to the bacterial elicitor harpin, although these transcripts are not induced by aluminium alone. The priming effect of aluminium depends on actin, and is accompanied by activation of genes linked with aluminium tolerance. As a result, the cell-death response to harpin is mitigated, again depending on actin filaments. We discuss these findings in the context of a working model, where actin remodelling (triggered by aluminium) can promote defence signalling independently of a Hypersensitive Response and discuss potential implications for the use of priming in sustainable viticulture.